Sewage treatment agent and preparation method thereof

The sewage treatment agent addresses low adsorption and photocatalytic efficiency by polymerizing specific compounds on modified porous magnetic ceramsite, enhancing adsorption and photocatalytic degradation while facilitating easy separation and recovery.

CN119176607AInactive Publication Date: 2024-12-24ZHONG RUI ENVIRONMENTAL PROTECTION CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411487851.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2024-12-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing sewage treatment technologies face challenges such as low adsorption capacity, poor stability, single function, and difficult separation and recovery of adsorbents, as well as the inefficiency of photocatalysts like nano-titanium dioxide in water treatment.

Method used

A sewage treatment agent is prepared by polymerizing 2,6-diaminonaphthalene and 1,3,6,8-tetrakis(4-formaldehydephenyl)perylene on the surface of modified porous magnetic ceramsite, which is obtained by polymerizing methyl acrylate and acrylamide on the surface and in the pores of porous magnetic ceramsite, and then hydrolyzing with sodium hydroxide.

Benefits of technology

The treatment agent achieves enhanced adsorption and photocatalytic degradation performance, with improved separation and recovery capabilities due to its magnetic properties and increased specific surface area, and effective pollutant removal through chemical and physical interactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005099169250000081
    Figure BDA0005099169250000081
Patent Text Reader

Abstract

The invention discloses a sewage treatment agent and a preparation method thereof, and relates to the field of sewage treatment. When the sewage treatment agent is prepared, firstly, clay and a mixed ferric salt solution are mixed, coprecipitation is performed under the action of sodium hydroxide, and then porous magnetic ceramsite is prepared through high-temperature calcination; secondly, polymerization of methyl acrylate on the surface and in pores of the porous magnetic ceramsite is initiated by heat, polymerization of acrylamide on the surface of the porous magnetic ceramsite is initiated by light, and modified porous magnetic ceramsite is prepared; finally, 2, 6-diaminonaphthalene and 1, 3, 6, 8-tetra (4-formylphenyl) perylene are polymerized on the surface of the modified porous magnetic ceramsite, and then the sewage treatment agent is obtained through alkaline hydrolysis. The sewage treatment agent prepared by the invention has good adsorption performance and photocatalytic degradation performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of sewage treatment, in particular to a sewage treatment agent and a preparation method thereof. Background Art

[0002] With the rapid development of industrialization and urbanization, the discharge of domestic sewage and industrial wastewater has increased dramatically. These sewage contain various complex components, including heavy metal ions, toxic dyes, antibiotics, food additives and other organic matter, which pose a threat to the natural environment and human health. There are many sewage treatment technologies in the existing technology, such as chemical precipitation, ion exchange, photocatalysis and adsorption.

[0003] The adsorption method removes pollutants by promoting the adsorption of pollutants on the surface of the adsorbent. It has high removal efficiency and strong adsorbent regeneration ability, but existing conventional adsorbents have problems such as low adsorption capacity, poor stability, single function, and difficult separation and recovery. Photocatalytic technology can effectively degrade some pollutants into non-toxic small molecules such as carbon dioxide and water, so that sewage can meet the requirements of no harmful emissions. However, some photocatalysts such as nano-titanium dioxide have small particle size and low density, and are not easy to separate from water after sewage treatment. Magnetic separation technology has emerged in the field of sewage treatment as an emerging water treatment technology. Magnetic materials used in sewage treatment have the advantage of zero energy separation. Therefore, combining multiple sewage treatment methods can give full play to the unique advantages of each method and improve the efficiency of sewage treatment. Summary of the invention

[0004] The purpose of the present invention is to provide a sewage treatment agent and a preparation method thereof to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A sewage treatment agent is provided, which is obtained by polymerizing 2,6-diaminonaphthalene and 1,3,6,8-tetrakis(4-formaldehydephenyl)perylene on the surface of modified porous magnetic ceramsite and then hydrolyzing with sodium hydroxide.

[0007] As an optimization, the modified porous magnetic ceramsite is obtained by polymerizing methyl acrylate on the surface and in the pores of the porous magnetic ceramsite and polymerizing acrylamide on the surface.

[0008] As an optimization, the porous magnetic ceramsite is obtained by mixing clay and a mixed iron salt solution, adding sodium hydroxide, and then calcining at a high temperature.

[0009] A method for preparing a sewage treatment agent comprises the following preparation steps:

[0010] (1) Clay and pure water are mixed at a mass ratio of 3:10 to obtain a clay dispersion, a mixed iron salt solution and a clay dispersion are mixed at a mass ratio of 1:(2-3) for 5-10 minutes, a 10M sodium hydroxide solution of 3-4 times the mass of the mixed iron salt solution is added, and the mixture is stirred at a speed of 100-200 r / min for 60 minutes to prepare a raw material ball with a particle size of 5 mm, the raw material ball is dried at 267 Pa and 90° C. for 12 hours, and then placed in a muffle furnace for calcination according to a temperature increase program to obtain a porous magnetic ceramsite;

[0011] (2) immersing the porous magnetic ceramsite in an acrylate solution, allowing it to stand for 30 minutes, and then filtering, repeating the immersion-filtration process 3-4 times, allowing it to stand for 2-3 hours at 80° C., immersing it again in an acrylamide solution, allowing it to stand for 30 minutes, filtering it, and irradiating it under a 365 nm ultraviolet lamp for 1-2 hours, with the lamp source distance being 5 cm, to obtain a modified porous magnetic ceramsite;

[0012] (3) The modified porous magnetic ceramsite, 2,6-diaminonaphthalene, 1,3,6,8-tetrakis(4-formaldehydephenyl)perylene and 1,4-dioxane are mixed, tetrakis(triphenylphosphine)palladium(0) is added, and the mixture is refluxed at 120°C for 40-42 hours. After cooling to room temperature, the mixture is filtered and added to a 10% by mass sodium hydroxide solution, and the mixture is reacted at 100°C for 5-6 hours. After the reaction is completed, the mixture is filtered and washed with pure water for 5-7 times, and dried at 60°C for 12 hours to obtain a sewage treatment agent.

[0013] As an optimization, the preparation method of the mixed iron salt solution in step (1) is: stir and mix ferric chloride hexahydrate, ferric chloride tetrahydrate and pure water in a mass ratio of 1:0.37:10 for 10 minutes to obtain a mixed iron salt solution.

[0014] As an optimization, the clay particle size in step (1) is 500-700 mesh.

[0015] As an optimization, the temperature rising program in step (1) is to heat to 600°C for calcination for 1 hour, heat to 800°C for calcination for 1 hour, and then heat to 950°C for calcination for 1 hour, and the heating rate is 10°C / min.

[0016] As an optimization, the acrylate solution in step (2) is obtained by mixing methyl acrylate, a thermal initiator, and dimethyl sulfoxide in a mass ratio of 1:0.02:20; the acrylamide solution is obtained by mixing acrylamide, a photoinitiator, and dimethyl sulfoxide in a mass ratio of 1:0.02:20; the thermal initiator is azobisisobutyronitrile; and the photoinitiator is 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methylacetone.

[0017] As an optimization, the mass ratio of the modified porous magnetic ceramsite, 2,6-diaminonaphthalene, 1,3,6,8-tetrakis(4-formaldehydephenyl)perylene, 1,4-dioxane, and tetrakis(triphenylphosphine)palladium(0) in step (3) is 1:(0.6-0.8):(0.2-0.3):(20-30):(0.03-0.05).

[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0019] When preparing the sewage treatment agent, the present invention comprises the following steps: firstly, clay and a mixed iron salt solution are mixed, and co-precipitated under the action of sodium hydroxide, and then calcined at high temperature to obtain porous magnetic ceramsite; secondly, methyl acrylate is polymerized on the surface and in the pores of the porous magnetic ceramsite by heat initiation, and acrylamide is polymerized on the surface of the porous magnetic ceramsite by light initiation to obtain modified porous magnetic ceramsite; finally, 2,6-diaminonaphthalene and 1,3,6,8-tetrakis(4-formaldehydephenyl)perylene are polymerized on the surface of the modified porous magnetic ceramsite, and then the sewage treatment agent is obtained by alkaline hydrolysis.

[0020] First, clay and a mixed iron salt solution are mixed, co-precipitated under the action of sodium hydroxide, and then calcined at high temperature to obtain porous magnetic ceramsite; clay and a mixed iron salt solution are mixed, co-precipitated under the action of sodium hydroxide, so that the generated magnetic ferroferric oxide particles can be evenly dispersed in the clay to avoid agglomeration, thereby giving the sewage treatment agent magnetism, which is beneficial to the separation of pollutants; after the clay is made into ceramsite, its specific surface area is significantly increased, and a rich porous structure can be formed inside, which is beneficial for the harmful substances in the sewage to fully contact with the surface of the ceramsite, thereby improving the adsorption efficiency;

[0021] Secondly, the modified porous magnetic ceramsite is prepared by thermally initiating the polymerization of methyl acrylate on the surface and in the pores of the porous magnetic ceramsite and by photoinitiating the polymerization of acrylamide on the surface of the porous magnetic ceramsite. The porous magnetic ceramsite is immersed in an acrylate solution containing a thermal initiator, and the surface and pores of the porous magnetic ceramsite are both covered with acrylate monomers. The high temperature initiates the polymerization of the acrylate monomers on the surface and in the pores. In the subsequent sodium hydroxide hydrolysis process, methyl acrylate is hydrolyzed into carboxyl groups, which can attract positively charged pollutants in sewage. The porous magnetic ceramsite is immersed again in an acrylamide solution containing a photoinitiator. Under light conditions, only the acrylamide monomers on the surface of the ceramsite will participate in the polymerization, and a polyacrylamide polymer containing an amide side chain is formed on the surface of the porous magnetic ceramsite. As a high molecular weight polymer, the molecular chain of the polymer can chemically react or physically adsorb with suspended matter, colloidal substances and organic pollutants in water, thereby improving the adsorption performance of the sewage treatment agent.

[0022] Finally, 2,6-diaminonaphthalene and 1,3,6,8-tetrakis(4-formaldehyde phenyl)perylene are polymerized on the surface of modified porous magnetic ceramsite and then hydrolyzed with alkaline to obtain a sewage treatment agent. 2,6-diaminonaphthalene undergoes a Schiff base reaction with the aldehyde group on 1,3,6,8-tetrakis(4-formaldehyde phenyl)perylene to generate a pyrene-based conjugated polymer on the surface of porous magnetic ceramsite. The Schiff base has a good complexing effect on metals and can adsorb metal ions in sewage. The conjugated polymer has a good light absorption capacity because it has more delocalized π electrons. The larger conjugated area of ​​the pyrene-based conjugated polymer is not only conducive to the free transmission of delocalized π electrons between layers, thereby improving the efficiency of the photocatalytic degradation reaction, but also can adsorb some organic pollutants that also have a π conjugated structure, such as organic dyes, thereby improving the photocatalytic degradation and adsorption properties of the sewage treatment agent. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] The clay particle size used in the following examples and comparative examples is 500-700 mesh; the thermal initiator used is azobisisobutyronitrile; the photoinitiator used is 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methylacetone; the acrylate solution used is a mixture of methyl acrylate, thermal initiator, and dimethyl sulfoxide in a mass ratio of 1:0.02:20, and the acrylamide solution used is a mixture of acrylamide, photoinitiator, and dimethyl sulfoxide in a mass ratio of 1:0.02:20; the heating program used is heating to 600° C. for calcination for 1 h, heating to 800° C. for calcination for 1 h, and then heating to 950° C. for calcination for 1 h, and the heating rate is 10° C. / min.

[0025] Embodiment 1:

[0026] A sewage treatment agent comprises the following preparation steps:

[0027] (1) Hexahydrate ferric chloride, tetrahydrate ferric chloride and pure water are stirred and mixed at a mass ratio of 1:0.37:10 for 10 minutes to obtain a mixed iron salt solution; clay and pure water are mixed at a mass ratio of 3:10 to obtain a clay dispersion; the mixed iron salt solution and the clay dispersion are mixed at a mass ratio of 1:2 for 10 minutes, a 10M sodium hydroxide solution of 3 times the mass of the mixed iron salt solution is added, and a raw material ball with a particle size of 5 mm is prepared after stirring at a speed of 200 r / min for 60 minutes, and the raw material ball is dried at 267 Pa and 90° C. for 12 hours, and then placed in a muffle furnace and calcined according to a temperature increase program to obtain porous magnetic ceramsite;

[0028] (2) immersing the porous magnetic ceramsite in an acrylate solution, allowing it to stand for 30 minutes, and then filtering it, repeating the immersion-filtration process three times, allowing it to stand for 3 hours at 80° C., immersing it again in an acrylamide solution, allowing it to stand for 30 minutes, filtering it, and irradiating it under a 365 nm ultraviolet lamp for 2 hours, with the lamp source distance being 5 cm, to obtain a modified porous magnetic ceramsite;

[0029] (3) Weighing the modified porous magnetic ceramsite, 2,6-diaminonaphthalene, 1,3,6,8-tetrakis(4-formaldehyde phenyl)perylene, 1,4-dioxane, and tetrakis(triphenylphosphine)palladium(0) in a mass ratio of 1:0.6:0.2:20:0.03; mixing the modified porous magnetic ceramsite, 2,6-diaminonaphthalene, 1,3,6,8-tetrakis(4-formaldehyde phenyl)perylene, and 1,4-dioxane, adding tetrakis(triphenylphosphine)palladium(0), reflux reacting at 120°C for 42h, cooling to room temperature, filtering, adding to a 10% by mass sodium hydroxide solution, reacting at 100°C for 6h, filtering after the reaction, washing with pure water 7 times, and drying at 60°C for 12h to obtain a sewage treatment agent.

[0030] Embodiment 2:

[0031] A sewage treatment agent comprises the following preparation steps:

[0032] (1) Hexahydrate ferric chloride, tetrahydrate ferric chloride and pure water are stirred and mixed at a mass ratio of 1:0.37:10 for 10 minutes to obtain a mixed iron salt solution; clay and pure water are mixed at a mass ratio of 3:10 to obtain a clay dispersion; the mixed iron salt solution and the clay dispersion are mixed at a mass ratio of 1:2.5 for 7 minutes; a 10M sodium hydroxide solution of 3.5 times the mass of the mixed iron salt solution is added; the mixture is stirred at a speed of 150 r / min for 60 minutes to prepare a raw material ball with a particle size of 5 mm; the raw material ball is dried at 267 Pa and 90° C. for 12 hours, and then placed in a muffle furnace and calcined according to a temperature increase program to obtain a porous magnetic ceramsite;

[0033] (2) immersing the porous magnetic ceramsite in an acrylate solution, allowing it to stand for 30 minutes, and then filtering it, repeating the immersion-filtration process three times, allowing it to stand for 2.5 hours at 80° C., immersing it again in an acrylamide solution, allowing it to stand for 30 minutes, filtering it, and irradiating it under a 365 nm ultraviolet lamp for 1.5 hours, with the lamp source distance being 5 cm, to obtain a modified porous magnetic ceramsite;

[0034] (3) Weighing the modified porous magnetic ceramsite, 2,6-diaminonaphthalene, 1,3,6,8-tetrakis(4-formaldehyde phenyl)perylene, 1,4-dioxane, and tetrakis(triphenylphosphine)palladium(0) in a mass ratio of 1:0.7:0.25:25:0.04; mixing the modified porous magnetic ceramsite, 2,6-diaminonaphthalene, 1,3,6,8-tetrakis(4-formaldehyde phenyl)perylene, and 1,4-dioxane, adding tetrakis(triphenylphosphine)palladium(0), reflux reacting at 120°C for 41h, cooling to room temperature, adding to a 10% by mass sodium hydroxide solution, reacting at 100°C for 5.5h, filtering after the reaction, washing with pure water for 6 times, and drying at 60°C for 12h to obtain a sewage treatment agent.

[0035] Embodiment 3:

[0036] A sewage treatment agent comprises the following preparation steps:

[0037] (1) Hexahydrate ferric chloride, tetrahydrate ferric chloride and pure water are stirred and mixed at a mass ratio of 1:0.37:10 for 10 minutes to obtain a mixed iron salt solution; clay and pure water are mixed at a mass ratio of 3:10 to obtain a clay dispersion; the mixed iron salt solution and the clay dispersion are mixed at a mass ratio of 1:3 for 5 minutes; a 10M sodium hydroxide solution of 4 times the mass of the mixed iron salt solution is added; the mixture is stirred at a speed of 100 r / min for 60 minutes to prepare a raw material ball with a particle size of 5 mm; the raw material ball is dried at 267 Pa and 90° C. for 12 hours, and then placed in a muffle furnace and calcined according to a temperature increase program to obtain a porous magnetic ceramsite;

[0038] (2) immersing the porous magnetic ceramsite in an acrylate solution, allowing it to stand for 30 minutes, and then filtering it, repeating the immersion-filtration process for 4 times, allowing it to stand for 2 hours at 80° C., immersing it again in an acrylamide solution, allowing it to stand for 30 minutes, filtering it, and irradiating it under a 365 nm ultraviolet lamp for 1 hour, with the lamp source distance being 5 cm, to obtain a modified porous magnetic ceramsite;

[0039] (3) Weighing the modified porous magnetic ceramsite, 2,6-diaminonaphthalene, 1,3,6,8-tetrakis(4-formaldehyde phenyl)perylene, 1,4-dioxane, and tetrakis(triphenylphosphine)palladium(0) in a mass ratio of 1:0.8:0.3:30:0.05; mixing the modified porous magnetic ceramsite, 2,6-diaminonaphthalene, 1,3,6,8-tetrakis(4-formaldehyde phenyl)perylene, and 1,4-dioxane, adding tetrakis(triphenylphosphine)palladium(0), reflux reacting at 120°C for 40h, cooling to room temperature, adding to a 10% by mass sodium hydroxide solution, reacting at 100°C for 5h, filtering after the reaction, washing with pure water 5 times, and drying at 60°C for 12h to obtain a sewage treatment agent.

[0040] Comparative Example 1:

[0041] The difference between the preparation method of the sewage treatment agent of Comparative Example 1 and Example 2 is that step (2) is modified as follows: immersing the porous magnetic ceramsite in an acrylamide solution and letting it stand for 30 minutes, filtering and irradiating it under a 365nm ultraviolet lamp for 1.5 hours, with the lamp source distance of 5 cm, to obtain modified porous magnetic ceramsite.

[0042] Comparative Example 2:

[0043] The difference between the preparation method of the sewage treatment agent of Comparative Example 2 and that of Example 2 lies in step (3), in which step (3) is modified as follows: weigh the modified porous magnetic ceramsite, 1,4-dioxane and tetrakis(triphenylphosphine)palladium(0) in a mass ratio of 1:25:0.04; mix the modified porous magnetic ceramsite and 1,4-dioxane, add tetrakis(triphenylphosphine)palladium(0), reflux at 120°C for 41h, cool to room temperature, add to a 10% sodium hydroxide solution by mass, react at 100°C for 5.5h, filter after the reaction and wash with pure water 6 times, and dry at 60°C for 12h to obtain a sewage treatment agent.

[0044] Comparative Example 3:

[0045] The difference between the preparation method of the sewage treatment agent of Comparative Example 3 and Example 2 lies in step (1), in which step (1) is modified to mix clay and pure water in a mass ratio of 3:10 to obtain a clay dispersion, stir and mix ferric chloride hexahydrate, ferric chloride tetrahydrate and pure water in a mass ratio of 1:0.37:10 for 10 minutes to obtain a mixed iron salt solution, add 10M sodium hydroxide solution (3.5 times the mass of the mixed iron salt solution) to the mixed iron salt solution, stir at a speed of 150r / min for 60 minutes, add 2.5 times the mass of the mixed iron salt solution and mix for 7 minutes to prepare a raw material ball with a particle size of 5 mm, dry the raw material ball at 267Pa and 90°C for 12 hours, and then place it in a muffle furnace and calcine according to a heating program to obtain a porous magnetic ceramsite.

[0046] Test Example 1:

[0047] Adsorption performance test:

[0048] Copper sulfate pentahydrate was prepared into a 5 mg / L copper ion solution; the sewage treatment agent prepared in the embodiment and the comparative example and the copper ion solution were mixed at a mass ratio of 1:40, and oscillated at 120 rpm for 120 min at 30° C., and then the precipitate was separated by a magnet, the supernatant was collected, and the copper ion content in the supernatant was determined by flame atomic absorption spectrometry, and the copper ion removal rate was calculated. The results are shown in Table 1.

[0049] Photocatalytic degradation performance test:

[0050] The sewage treatment agent prepared in the embodiment and the comparative example and 50 mg / L rhodamine B solution were mixed at a mass ratio of 1:1 for 20 minutes, and a photocatalytic degradation experiment was carried out using a YM-GHX-I photocatalytic reactor. The light source was a 300W xenon lamp, the emission wavelength range of the xenon lamp was 360-780nm, and the light source was 10 cm away. Then, the precipitate was separated by a magnet, the supernatant was collected, the rhodamine B concentration was determined by spectrophotometry, and the degradation rate of rhodamine B was calculated. The results are shown in Table 1.

[0051] Test of recovery rate of sewage treatment agent:

[0052] The precipitate separated by the magnet in the adsorption performance test was immersed in a hydrochloric acid solution with a concentration of 0.1 mol / L, shaken at 30°C and 100 rpm for 24 hours, filtered and dried at 105°C for 1 hour, and weighed. The recovery rate of the sewage treatment agent was calculated based on the mass of the precipitate and the mass of the sewage treatment agent input. The results are shown in Table 1.

[0053] Table 1

[0054]

[0055]

[0056] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 2 in Table 1, it can be found that the sewage treatment agent prepared by the present invention has good adsorption performance and photocatalytic degradation performance.

[0057] By comparison, the copper ion removal rate of Examples 1 to 3 is greater than that of Comparative Examples 1 to 2, and the degradation rate of Rhodamine B in Examples 1 to 3 is greater than that of Rhodamine B in Comparative Example 2, indicating that the clay and the mixed iron salt solution are first mixed, co-precipitated under the action of sodium hydroxide, and then calcined at high temperature to obtain porous magnetic ceramsite; the clay and the mixed iron salt solution are mixed, and co-precipitated under the action of sodium hydroxide, so that the generated magnetic ferroferric oxide particles can be evenly dispersed in the clay to avoid agglomeration, thereby giving the sewage treatment agent magnetism, which is beneficial to the separation of pollutants; after the clay is made into ceramsite, its specific surface area is significantly increased, and a rich porous structure can be formed inside, which is beneficial to the full contact between harmful substances in sewage and the surface of ceramsite, thereby improving the adsorption efficiency; secondly, the polymerization of methyl acrylate on the surface and pores of the porous magnetic ceramsite is initiated by heat, and the photoinduced The porous magnetic ceramsite is polymerized on the surface of the porous magnetic ceramsite to obtain the modified porous magnetic ceramsite; the porous magnetic ceramsite is immersed in an acrylic acid ester solution containing a thermal initiator, and the surface and pores of the porous magnetic ceramsite are all stained with acrylic acid ester monomers. The high temperature initiates the polymerization of the acrylic acid ester monomers on the surface and in the pores. In the subsequent sodium hydroxide hydrolysis process, the methyl acrylate is hydrolyzed into carboxyl groups, which can attract positively charged pollutants in the sewage; the porous magnetic ceramsite is immersed in an acrylic acid amide solution containing a photoinitiator again. Under light conditions, only the acrylamide monomers on the surface of the ceramsite will participate in the polymerization, and a polyacrylamide polymer containing an amide side chain is formed on the surface of the porous magnetic ceramsite. As a high molecular weight polymer, the molecular chain of the polymer can chemically react or physically adsorb with suspended matter, colloidal substances and organic pollutants in water, thereby improving the adsorption performance of the sewage treatment agent. Finally, 2,6-diaminonaphthalene and 1,3,6,8-tetrakis(4-formaldehyde phenyl)perylene are polymerized on the surface of modified porous magnetic ceramsite and then hydrolyzed with alkaline to obtain a sewage treatment agent. 2,6-diaminonaphthalene undergoes a Schiff base reaction with the aldehyde group on 1,3,6,8-tetrakis(4-formaldehyde phenyl)perylene to generate a pyrene-based conjugated polymer on the surface of porous magnetic ceramsite. The Schiff base has a good complexing effect on metals and can adsorb metal ions in sewage. The conjugated polymer has a good light absorption capacity because it has more delocalized π electrons. The larger conjugated area of ​​the pyrene-based conjugated polymer is not only conducive to the free transmission of delocalized π electrons between layers, thereby improving the efficiency of the photocatalytic degradation reaction, but also can adsorb some organic pollutants that also have a π conjugated structure, such as organic dyes, thereby improving the photocatalytic degradation and adsorption properties of the sewage treatment agent.

[0058] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A sewage treatment agent, characterized in that: The sewage treatment agent is obtained by polymerizing 2,6-diaminonaphthalene and 1,3,6,8-tetrakis(4-formaldehyde phenyl)perylene on the surface of modified porous magnetic ceramsite and then hydrolyzing with sodium hydroxide; The modified porous magnetic ceramsite is obtained by polymerizing methyl acrylate on the surface and in the pores of the porous magnetic ceramsite and polymerizing acrylamide on the surface; The porous magnetic ceramsite is obtained by mixing clay and a mixed iron salt solution, adding sodium hydroxide, and then calcining at high temperature.

2. A method for preparing a sewage treatment agent, characterized in that: The method comprises the following preparation steps: (1) Clay and pure water are mixed at a mass ratio of 3:10 to obtain a clay dispersion, a mixed iron salt solution and a clay dispersion are mixed at a mass ratio of 1:(2-3) for 5-10 minutes, a 10M sodium hydroxide solution of 3-4 times the mass of the mixed iron salt solution is added, and the mixture is stirred at a speed of 100-200 r / min for 60 minutes to prepare a raw material ball with a particle size of 5 mm, the raw material ball is dried at 267 Pa and 90° C. for 12 hours, and then placed in a muffle furnace for calcination according to a temperature increase program to obtain a porous magnetic ceramsite; (2) immersing the porous magnetic ceramsite in an acrylate solution, allowing it to stand for 30 minutes, and then filtering, repeating the immersion-filtration process 3-4 times, allowing it to stand for 2-3 hours at 80° C., immersing it again in an acrylamide solution, allowing it to stand for 30 minutes, filtering it, and irradiating it under a 365 nm ultraviolet lamp for 1-2 hours, with the lamp source distance being 5 cm, to obtain a modified porous magnetic ceramsite; (3) The modified porous magnetic ceramsite, 2,6-diaminonaphthalene, 1,3,6,8-tetrakis(4-formaldehydephenyl)perylene and 1,4-dioxane are mixed, tetrakis(triphenylphosphine)palladium(0) is added, and the mixture is refluxed at 120°C for 40-42 hours. After cooling to room temperature, the mixture is filtered and added to a 10% by mass sodium hydroxide solution, and the mixture is reacted at 100°C for 5-6 hours. After the reaction is completed, the mixture is filtered and washed with pure water for 5-7 times, and dried at 60°C for 12 hours to obtain a sewage treatment agent.

3. The method for preparing a sewage treatment agent according to claim 2, characterized in that: The preparation method of the mixed iron salt solution in step (1) is as follows: ferric chloride hexahydrate, ferric chloride tetrahydrate and pure water are stirred and mixed in a mass ratio of 1:0.37:10 for 10 minutes to obtain a mixed iron salt solution.

4. The method for preparing a sewage treatment agent according to claim 2, characterized in that: The clay particle size in step (1) is 500-700 mesh.

5. The method for preparing a sewage treatment agent according to claim 2, characterized in that: The temperature rising program of step (1) is to heat to 600°C for calcination for 1 hour, heat to 800°C for calcination for 1 hour, and then heat to 950°C for calcination for 1 hour, and the heating rate is 10°C / min.

6. The method for preparing a sewage treatment agent according to claim 2, characterized in that: The acrylate solution in step (2) is obtained by mixing methyl acrylate, a thermal initiator and dimethyl sulfoxide in a mass ratio of 1:0.02:20; the acrylamide solution is obtained by mixing acrylamide, a photoinitiator and dimethyl sulfoxide in a mass ratio of 1:0.02:20; the thermal initiator is azobisisobutyronitrile; and the photoinitiator is 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methylacetone.

7. The method for preparing a sewage treatment agent according to claim 2, characterized in that: The mass ratio of the modified porous magnetic ceramsite, 2,6-diaminonaphthalene, 1,3,6,8-tetrakis(4-formaldehydephenyl)perylene, 1,4-dioxane and tetrakis(triphenylphosphine)palladium(0) in step (3) is 1:(0.6-0.8):(0.2-0.3):(20-30):(0.03-0.05).

Citation Information

Cited By

  • Magnetic porous loess organic composite material as well as preparation method and application thereof

    CN122057484A